Impact of Privatization on Economic Development In India: Examining the Advantages and Disadvantages of Privatization in India (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Privatization in generic terms refers to the process oftransfer of ownership, can be of both permanent or long term lease in nature,of a once upon a time state-owned or public owned property to individuals orgroups that intend to utilize it for private benefits and run the entity withthe aim of profit maximization. In other words, it is a route from public orstate ownership to private players or a group. From the other point of view, itis a strategy that provides advantages to a few at the price of many. However,this is always subjected to the circumstances involved. In this paper, the aimis to understand the major advantages and disadvantages of privatization andimpact of privatization in this country.